(3GdeWGdH GdEdgjIs - (3GdJhbGJj GdQhej GdMfaj, dWa Gddg (B" (3dWaj (B" (3Hf MSf, J (B904s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf agPg bhGYO JLQj eLQi GdTQM dQSGdJfG GdeYehdI aj HjGf GdehVhYGJ hGddg Gdehab hHg GdahR (B, (3bhdg GdYdhe GdYQHjI jSei LfS GdYQHjI HGdYQHjI hdYde GdCOH hHGdCOH s
(3BNQgG (B:s
(3bhdg Ydi ePgH Cgd GdSfI ETGQI Edi Cf GdaQb GdeNGdaI ddePgH GdeYJRdI hGdcQGejI hGdTjYI dge Ydhe TQYjI eeGKdI deG PcQ ef GdYdhe hdG jJYdb HgG ZQVfG JeJ MGTjI Gdehdi GdaGVds
(3efbhdI Yf fSNI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ MGLj NdjaI Cfg obJd YGe (B900 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\242s
(3cTa GdXfhf(B2\ 1905s
Keywords: (3GdagGQS hGdecJHGJs